Topical application of mitomycin-C in corrosive esophageal strictures - Kumar Arun; Bhatnagar V (Wolters Kluwer Medknow Publications, 2005)
Introduction: Corrosive ingestion is the major cause of esophageal stricture in our country. Mitomycin-C, an anthracycline derived from Streptomyces caespitosus, has both antineoplastic and antiproliferative properties. Use of mitomycin-C have been well documented in various ophthalmologic procedures and laryngo-tracheal conditions where it has been shown that mitomycin-C inhibited fibroblast proliferation during the postoperative phase without damaging the mucosal and epithelial growth. This preliminary report documents the use of mitomycin-C in caustic stricture esophagus. Materials and Methods: A prospective study was carried out in ten known patients of caustic esophageal strictures. After taking informed consent patients were subjected to antegrade or retrograde esophageal dilatation under general anesthesia and mitomycin-C was applied topically by a 10 mm cottonoid sponge soaked in mitomycin-C solution (0.4 mg/ml) for 5 minutes at the stricture site. The procedure was repeated at 4 weekly intervals thereafter and need for further dilatation was assessed. Outcomes in terms of symptomatic relief and radiological evaluation were assessed after therapy and results were analyzed for effectiveness of mitomycin-C and compared with retrospective results of previous cases of corrosive ingestion managed at the same institution. Results: Total number of dilatations required were 34 (mean - 3.4) Two patients required single dilatation while two required six sessions. Symptomatic as well as radiological improvement was present in nine patients. Conclusions: Use of mitomycin-C seems to improve the outcome in patients of corrosive esophageal strictures. Patients who have undergone esophageal replacement also seem to benefit from mitomycin-C.